Delayed left traumatic diaphragmatic hernia mimicking acute coronary syndrome (Indian Journal of Case Reports, 2020)
Traumatic diaphragmatic hernias (DH) represent only a small percentage of all DH. Injury is mostly caused by severe blunt or penetrating trauma. DH may be recognized during the period of hospitalization immediately following trauma. Here, we present the case of DH in a 33-year-old male who presented with typical acute coronary syndrome-related symptoms with significant electrocardiography changes. The case is unique due to the occurrence of the DH with trauma and its delayed presentation with acute coronary symptoms. A high index of suspicion should be raised if the patient had a previous history of trauma and chest X-ray findings.